2020
DOI: 10.26434/chemrxiv.13114019.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Temperature and Solvent Effects on H2 Splitting and Hydricity: Ramifications on CO2 Hydrogenation by a Rhenium Pincer Catalyst

Abstract: The catalytic hydrogenation of carbon dioxide holds immense promise for applications in sustainable fuel synthesis and hydrogen storage. Mechanistic studies that connect thermodynamic parameters with the kinetics of catalysis can provide new understanding and guide predictive design of improved catalysts. Reported here are thermochemical and kinetic analyses of a new pincer-ligated rhenium complex (<sup>tBu</sup>POCOP)Re(CO)<sub>2</sub>(<sup>tBu</sup>POCOP = 2,6-bis(di-<i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Similarly, very recently Miller and coworkers demonstrated that if the kinetic energy barrier for hydride formation is very low, then the following hydride transfer step should give higher rate even at low temperature due to accumulation of hydride intermediate. 48 The observed rate (k obs or TOF) for hydride transfer to CO 2 can be thought of then in the simplest terms, as determined by both the kinetic enhancement due to high concentration of (H-1) 3and also from the thermochemical driving force related to the hydricity of (H-1) 3-. Hydricity (∆G H-) is the free energy for loss of hydride from a hydride donor such as (H-1) 3-, and -absent kinetic effects -a linear free energy relationship (LFER) exists between Log(TOF/ s -1 ) and E cat/2 over a series of catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, very recently Miller and coworkers demonstrated that if the kinetic energy barrier for hydride formation is very low, then the following hydride transfer step should give higher rate even at low temperature due to accumulation of hydride intermediate. 48 The observed rate (k obs or TOF) for hydride transfer to CO 2 can be thought of then in the simplest terms, as determined by both the kinetic enhancement due to high concentration of (H-1) 3and also from the thermochemical driving force related to the hydricity of (H-1) 3-. Hydricity (∆G H-) is the free energy for loss of hydride from a hydride donor such as (H-1) 3-, and -absent kinetic effects -a linear free energy relationship (LFER) exists between Log(TOF/ s -1 ) and E cat/2 over a series of catalysts.…”
Section: Resultsmentioning
confidence: 99%